Gen Z's Interest in Herbal Drinks as Part of Healthy Tourism - Ghani, Luthfi; Maryani, Enok; Andari, Rini (Graduate School, Universitas Brawijaya, 2023)
This study aims to analyze Generation Z's interest in herbal medicine as part of the development of health tourism in Indonesia. Supported by the Ministry of Tourism and Creative Economy and the Ministry of Health, wellness and herbal tourism has become one of the focuses in strengthening health tourism. The research method used is a descriptive qualitative approach with a purposive sampling technique. The sources consisted of ten herbal medicine producers and ten Gen Z individuals in the city of Bandung. The results of the study show that most Gen Z individuals are familiar with herbal medicine and understand its health benefits. However, there is still a stigma associated with herbal medicine, which is often perceived as having a bitter taste and being a drink for older people. Herbal medicine producers, such as Minuman Rempah Indonesia, have innovated by adding natural sweeteners to attract Gen Z. The gap in this study lies in the low interest of Gen Z in herbal medicine, despite the many innovations in taste made by producers. This study emphasizes the importance of continuous innovation in herbal medicine production to strengthen its position in the health tourism sector.